2018
DOI: 10.1097/mph.0000000000001134
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Ataxia-telangiectasia Presented With Hemophagocytic Syndrome

Abstract: Ataxia-telangiectasia (A-T) is a multisystem disease caused by a genetic defect located on the long arm of chromosome 11 (11p22-23). The gene defect results in the loss of A-T-mutated protein, subsequently leading to unrepaired DNA fractures and defects in the signal transduction pathway. As a result, characteristic findings arise, including recurrent sinopulmonary infections, hypersensitivity against ionized radiation with the tendency to develop cancer related to progressive cerebellar ataxia, pathognomonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Germ-line mutations in ATM, leading to genomic instability, defective DNA double-strand repair, and selective escape from apoptosis, can be seen as a DNA replication stress that promotes the development and progression of cancer [32,36,37]. Mehmet H et al, reported a 3-year-old male infant with A-T who developed HLH during follow-up [12]. Although there is no direct evidence that mutations in AP3B1 and ATM cause HLH, both are associated with HLH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Germ-line mutations in ATM, leading to genomic instability, defective DNA double-strand repair, and selective escape from apoptosis, can be seen as a DNA replication stress that promotes the development and progression of cancer [32,36,37]. Mehmet H et al, reported a 3-year-old male infant with A-T who developed HLH during follow-up [12]. Although there is no direct evidence that mutations in AP3B1 and ATM cause HLH, both are associated with HLH.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-two HLH cases with biallelic mutations in AP3B1 have been reported in the literature, with one patient developing lethal HLH [11], while the ATM gene was only reported in a 3-year-old male infant [12]. Herein, we report a case of a 14-year-old male diagnosed with fulminant HLH that might be associated with AP3B1 and ATM genes' mutation.…”
Section: Introductionmentioning
confidence: 90%
“…(19) Associated systemic findings include lung disease, radiation sensitivity, neurodevelopmental delay, skin conditions (hypertrichosis, seborrheic dermatitis, vitiligo, acanthosis nigricans), insulin-resistant diabetes mellitus and increased incidence of malignancy. (5) AT can appear in three different forms: Pure A-T, where patients have all or almost all of the diagnostic symptoms; attenuated or type II T-A, where patients lack some of the typical findings but have radio sensitivity; and carrier T-A, where patients with a single ATM gene mutation are at increased risk of developing cancer. 20Regarding diagnostic criteria, Delfino et al (8) and Lazo-Rivera & Pastor-Vizcarra, (21) in accordance with the Lederman's group from the Ataxia-telangiectasia Clinical Center, established three characteristic neurological findings of AT: A) ataxic gait at the ages of 2-3; B) dysarthria and oculomotor disorders such as apraxia; and C) associated movement disorders, progressive ataxia, hypomimia, swallowing disorders and peripheral neuropathy.…”
Section: Case Presentationmentioning
confidence: 99%
“…(2) Moreover, the cells of AT patients present chromosomal instability, hypersensitivity to X-rays, propensity to lymphoid neoplasms, variable immunodeficiency, and susceptibility to infections, which cause systemic symptoms such as endocrinopathies, leukemias, radiosensitivity and ocular telangiectasias. (3,4) While over 400 mutations of the ATM gene have been detected, it has been reported that AT has an incidence of 1 between 40 000 and 100 000 people (5) and that its frequency of heterozygosity in the mutant allele is 1.4% to 2% in the general population. (1,3) This disease is usually diagnosed late, as it is only identifiable when patients have severe symptoms that begin with alterations in the motor system.…”
Section: Introductionmentioning
confidence: 99%